DIFFERENCES IN HYPERTENSION PHENOTYPES BETWEEN AFRICANS AND EUROPEANS: ROLES OF INHERITANCE AND ENVIRONMENT. (April 2021) - Faconti, Luca; McNally, Ryan; Farukh, Bushra; Adeyemib, Olusoji; Cruickshankc, J. Kennedy; Wilkinson, Ian; Chowienczyk, Philip; Ojji, Dike
Abstract : Objective: Hypertension phenotypes differ in Africans and white Europeans, with a greater prevalence of low renin salt-sensitive hypertension and greater predisposition to adverse cardiac remodelling in Africans. We aim to elucidate roles of inheritance and environment in determining hypertension phenotypes in Africans born and resident in Nigeria (AA), sub-Saharan Africans living in the UK (AE) and white Europeans in the UK (EE). Design and method: 469 hypertensive subjects in the UK and Nigeria were enrolled. Biochemistry, blood pressure, left ventricular structure (echocardiography) and 24 h urinary collections of sodium and potassium were measured Results: 24-hour urinary sodium and potassium excretion were similar in AE and EE but lower in AA with a proportionately greater excretion of potassium compared to sodium in Africans resident in Europe compared to those in Africa (sodium excretion 46.9% greater in AE compared to AA and potassium excretion 109.8% greater in AE compared to AA, both P < 0.01) so that the ratio of sodium to potassium in the urine was higher in AA compared to both AE and EE. Plasma renin was lower in Africans irrespective of residency compared to white Europeans, but aldosterone was higher in Africans in Europe compared to those in Africa (466.15 ± 32.95 pmol/L vs 258.60 ± 17.42 pmol/L, P < 0.001). Left ventricular mass index adjusted for blood pressure was greatest in Africans in Europe (103.27 ± 2.32 g/m2) compared to those in Africa (89.28 ± 1.98 g/m2, P < 0.01) or white Europeans (86.77 ± 2.63 g/m2, P < 0.01). The difference between AE and AA was largely driven by a greater LV cavity size in AE compared to AA (difference in end diastolic diameter, 0.45 ± 0.056 cm, P < 0.001). Consequently, the RWT showed a trend to "eccentricity" moving from AA to AE. Conclusions: Both genetic and environmental differences contribute to phenotypic differences between Africans in Europe and white Europeans. A low renin state is predominantly genetically determined whereas higher aldosterone, related to higher potassium intake or another environmental factor, may contribute to greater LV mass in Africans in Europe.